2016
DOI: 10.5194/nhess-2016-10
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrodynamics of long-duration urban floods: experiments and numerical modelling

Abstract: Abstract. Flood risk in urbanized areas raises increasing concerns as a result of demographic and climate changes. Hydraulic modelling is a key component of urban flood risk analysis. Yet, detailed validation data are still lacking for comprehensively validating hydraulic modelling of inundation flow in urbanized floodplains. In this study, we present an experimental model of inundation flow in a typical European urban district and we compare the experimental observations with predictions by a shallow-water nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Moreover it quantifies the filtering effect of the topography on the discharge distribution through the whole district as suggested by [14] which is confirmed by the downstream discharge sensitivity to upstream inflow that is barely null. The sensitivity of downstream discharge repartition to a uniform roughness is shown to be relatively low on the tested configurations as suggested by [4] with forward SW model runs on a Cartesian grid. Concerning the street outlet discharge, different sensitivity patterns are obtained with a variance explained at 100% by the downstream water height, or almost equally explained by the downstream water height and the upstream faces discharge; the friction coefficient being only involved in some particular streets.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover it quantifies the filtering effect of the topography on the discharge distribution through the whole district as suggested by [14] which is confirmed by the downstream discharge sensitivity to upstream inflow that is barely null. The sensitivity of downstream discharge repartition to a uniform roughness is shown to be relatively low on the tested configurations as suggested by [4] with forward SW model runs on a Cartesian grid. Concerning the street outlet discharge, different sensitivity patterns are obtained with a variance explained at 100% by the downstream water height, or almost equally explained by the downstream water height and the upstream faces discharge; the friction coefficient being only involved in some particular streets.…”
Section: Discussionmentioning
confidence: 77%
“…2D SW models are able to model recirculation zones and mixing layers (recall with depth averaged velocities) and then the corresponding localized head losses, hence it is not necessary to account for those effects with the friction coefficient. The uniform roughness calibrated in this study for the 2D SW model (including a k − ε turbulence model as suggested by [4] for better simulating recirculation zones) is K 2D = 100m 1/3 .s −1 . This latest value is a good M A N U S C R I P T proof of 2D SW ability in reproducing such flows since it is very close to the "real experimental" one -recall 80 − 100m 1/3 .s −1 is expected for plexiglass.…”
Section: Head Losses Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydraulic models linked to computer‐aided design (CAD) or geographic information systems (GIS) systems provide spatial data for the evaluation and quantification of groundwater‐related hazard and its representation using computer mapping techniques (Büchele et al, 2006; Hughes et al, 2001; MacDonald, Bloomfield, et al, 2008; Morris, Cobby, Zaidman, & Fisher, 2015; Naughton, Johnston, McCormack, & Gill, 2015; Sommer, 2007). Such techniques are routinely applied in the development of flood risk management plans which take into account surface flooding (Arrault et al, 2016; CDS, 2013; Directive, 2007). However, there is a lack of studies focused on the mapping of the hazard induced by groundwater, namely due to the uplift on the topsoil layers during flood events.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been extensively validated and applied for simulating flow induced by dam and dike breaching (Dewals et al, 2011;Roger et al, 2009) as well as for conducting flood risk analysis (Arrault et al, 2016;Beckers et al, 2013;Bruwier et al, 2015;Detrembleur et al, 2015;Ernst et al, 2010). We detail below how friction was parametrized in the hydraulic model, as well as the prescribed boundary conditions and the modelling 155 procedure.…”
Section: Hydraulic Modellingmentioning
confidence: 99%